Cover Picture: The Role of a Dipeptide Outer‐Coordination Sphere on H2‐Production Catalysts: Influence on Catalytic Rates and Electron Transfer (Chem. Eur. J. 6/2013). Issue 6 (29th January 2013) - Reback, Matthew L.; Ginovska‐Pangovska, Bojana; Ho, Ming‐Hsun; Jain, Avijita; Squier, Thomas C.; Raugei, Simone; Roberts, John A. S.; Shaw, Wendy J.
<x xml:space="preserve">Abstract</x> Dipeptide‐based ligands on Ni(P2N2)2 hydrogen production catalysts can alter both the rate and the overpotential of the resulting catalyst. The figure shows an overlay of the trajectories from molecular dynamics simulations and highlights the flexibility of the dipeptide ligands, which may aid in transient delivery of protons, but also limits the precise positioning achieved in enzymes. For more details see the Full Paper by S. Raugei, J. A. S. Roberts, W. J. Shaw and co‐workers on page 1928 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>